The Mxi-Spa Type III Secretory Pathway of Shigella flexneri Requires an Outer Membrane Lipoprotein, MxiM, for Invasin Translocation - Schuch, Raymond (American Society for Microbiology, 1999)
Invasion of epithelial cells by Shigella flexneri is mediated by a set of translocated bacterial invasins, the Ipa proteins, and its dedicated type III secretion system, called Mxi-Spa. We show here that mxiM, part of the mxi-spa locus in the S. flexneri virulence plasmid, encodes an indispensable type III secretion apparatus component, required for both Ipa translocation and tissue culture cell invasion. We demonstrated that mature MxiM, first identified as a putative lipoprotein, is lipidated in vivo. Consistent with features of known lipoproteins, MxiM (i) can be labeled with [(3)H]palmitate and [2-(3)H]glycerol, (ii) is associated with the cell envelope, (iii) is secreted independently of the type III pathway, and (iv) requires an intact lipoprotein modification and processing site for full activity. The lipidated form of MxiM was detected primarily in the outer membrane, where it establishes a peripheral association with the inner leaflet. Through analysis of subcellular Ipa distribution in a mxiM null mutant background, MxiM was found to be required for the assembly and/or function of outer, but not inner, membrane regions of Mxi-Spa. This function probably requires interactions with other Mxi-Spa subunits within the periplasmic space. We discuss implications of these findings with respect to the function of MxiM and the structure of Mxi-Spa as a whole.